2010
DOI: 10.1186/1476-511x-9-27
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different formulas for LDL-C calculation

Abstract: BackgroundFriedewald's formula for the estimation of LDL-C concentration is the most often used formula in clinical practice. A recent formula by Anandaraja and colleagues for LDL-C estimation still needs to be evaluated before it is extensively applied in diagnosis. In the present study we validated existing formulas and derived a more accurate formula to determine LDL-C in a Serbian population.MethodsOur study included 2053 patients with TG ≤ 4.52 mmol/L. In an initial group of 1010 patients, Friedewald's an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
84
4
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(97 citation statements)
references
References 31 publications
7
84
4
2
Order By: Relevance
“…On calculating the mean percentage difference, it was found that MF-LDL-C differs by 3.5% from D-LDL-C, which was much lower in comparison to the other two calculated formulae (7.29 and 7.64% by F-LDL-C and A-LDL-C respectively). Similar differences were reported in the study by Kapoor 21 these differences were found to be 6.9 and 3.9% for Friedewald and Anandaraja methods respectively. Kamal et al 18 found that MF-LDL-C differs by 10.5% from D-LDL-C, which was much lower in comparison to the other two calculated formulae (16.7 and 22.35% by F-LDL-C and A-LDL-C respectively) similar to our study.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…On calculating the mean percentage difference, it was found that MF-LDL-C differs by 3.5% from D-LDL-C, which was much lower in comparison to the other two calculated formulae (7.29 and 7.64% by F-LDL-C and A-LDL-C respectively). Similar differences were reported in the study by Kapoor 21 these differences were found to be 6.9 and 3.9% for Friedewald and Anandaraja methods respectively. Kamal et al 18 found that MF-LDL-C differs by 10.5% from D-LDL-C, which was much lower in comparison to the other two calculated formulae (16.7 and 22.35% by F-LDL-C and A-LDL-C respectively) similar to our study.…”
Section: Discussionsupporting
confidence: 78%
“…[18][19][20] The correlation between D-LDL-C and A-LDL-C in our study was found to be 0.92, which was similar to that of other studies, i.e., correlation of 0.93, 0.89, and 0.81. 18,19,21 Our study found a correlation of 0.94 between MF-LDL-C and D-LDL-C, which was higher than the one found by Kamal et al 18 (r = 0.81) and similar to Kapoor et al 17 (r = 0.95). Table 5: Summary of the measurements of TC, LDL-C (direct), LDL-C (Friedewald), and HDL-C according to TG levels, presented as mean ± SD (lowest level found -greatest level found) with Friedewald formula.…”
Section: Discussioncontrasting
confidence: 55%
“…Although a good correlation exists between calculated LDL-C and M-LDL-C, the underestimation of LDL-C according to this formula has been shown in previous studies in the general population, as well as in those with diabetes mellitus. 20,21 Attempts to derive and validate further equations for LDL-C calculation have not been widely adopted, 22,23 and the Friedewald formula remains the recommended method in clinical practice and most National Lipid Guidelines. 4,5,24 Martin et al 25 after evaluating over 1.3 million lipid samples quantified by ultracentrifugation recently recommended an adjustable factor for the TG-to-VLDL ratio, instead of using a fixed factor of 5 (when using mg/dL), based on TG and non-HDL-cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…renal failure or diabetes) [2,11], but is widely used. Several other formulae have been developed, but these did not perform better than Friedewald's calculation [12][13][14] or had varying results in different population groups [10,[15][16][17][18][19] and including those considering TG ratios [20,21]. In the latest study validating a novel formula in comparison with Friedewald's calculation and the LDL-C reference method in 23 055 patients, the benefits over…”
Section: Introductionmentioning
confidence: 99%